Carbon encapsulated nickel nanoparticles synthesized by a modified alcohol catalytic chemical vapor deposition method - Singjai P. (2014)
In this work, a simple and cost-efficient method was demonstrated for the production of carbon encapsulated nickel nanoparticles (CENPs). The CENPs were synthesized from nickel oxide by a modified alcohol catalytic chemical vapor deposition method at atmospheric pressure. Structural characterizations using scanning electron microscopy, transmission electron microscopy and X-ray diffraction indicated that the Ni-core mean diameter and the graphite-layer mean thickness were 98 ± 31 nm and 65 ± 35 nm, respectively. Room temperature magnetization results showed a ferromagnetic behavior of the CENPs, in which the saturation magnetization decreased with decreasing the Ni-to-C ratio whereas the coercivity increased with decreasing the Ni-core diameter. © 2007 Elsevier B.V. All rights reserved.